2011
DOI: 10.1128/jvi.02022-10
|View full text |Cite
|
Sign up to set email alerts
|

Sheep with Scrapie and Mastitis Transmit Infectious Prions through the Milk

Abstract: Prions are misfolded proteins that are infectious and naturally transmitted, causing a fatal neurological disease in humans and animals. Prion shedding routes have been shown to be modified by inflammation in excretory organs, such as the kidney. Here, we show that sheep with scrapie and lentiviral mastitis secrete prions into the milk and infect nearly 90% of naïve suckling lambs. Thus, lentiviruses may enhance prion transmission, conceivably sustaining prion infections in flocks for generations. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 15 publications
3
43
0
1
Order By: Relevance
“…Em ambos os animais, estas lesões, apesar de mais evidentes no tronco encefálico ao nível do óbex, foram observadas também no mesencéfalo, ponte, medula oblonga, cornos laterais e ventrais da medula espinhal, concordando com as descrições de Summers et al (1995), Driemeier (2007), Maxie & Youssef (2007) Hoinville (1996), este teste é de grande utilidade para o diagnóstico da doença em animais recém-infectados, em fase de incubação ou com sinais iniciais da doença, quando as alterações histopatológicas ainda podem estar ausentes ou serem incipientes, com possibilidade de diagnóstico falso negativo na histopatologia. Neste caso, segundo Haritani et al (1994) (Thomzig et al 2007), leite (Konold et al 2008, Lacroux et al 2008, Maddison et al 2009, Ligios et al 2011, fezes (Tamgüney 2009;,Terry et al 2011), urina (Murayama et al 2007, Gregori et al 2008, Rubenstein et al 2011, saliva (Vascellari et al 2007, sangue (Murayama et al 2007, Edwards et al 2010 e secreções nasais (Bessen et al 2010). A placenta, segundo é via por onde o PrP sc é mais intensamente eliminado, mas as demais fontes não devem ser negligenciadas, ao se estabelecer medidas de controle sanitário da doença.…”
Section: Resultsunclassified
“…Em ambos os animais, estas lesões, apesar de mais evidentes no tronco encefálico ao nível do óbex, foram observadas também no mesencéfalo, ponte, medula oblonga, cornos laterais e ventrais da medula espinhal, concordando com as descrições de Summers et al (1995), Driemeier (2007), Maxie & Youssef (2007) Hoinville (1996), este teste é de grande utilidade para o diagnóstico da doença em animais recém-infectados, em fase de incubação ou com sinais iniciais da doença, quando as alterações histopatológicas ainda podem estar ausentes ou serem incipientes, com possibilidade de diagnóstico falso negativo na histopatologia. Neste caso, segundo Haritani et al (1994) (Thomzig et al 2007), leite (Konold et al 2008, Lacroux et al 2008, Maddison et al 2009, Ligios et al 2011, fezes (Tamgüney 2009;,Terry et al 2011), urina (Murayama et al 2007, Gregori et al 2008, Rubenstein et al 2011, saliva (Vascellari et al 2007, sangue (Murayama et al 2007, Edwards et al 2010 e secreções nasais (Bessen et al 2010). A placenta, segundo é via por onde o PrP sc é mais intensamente eliminado, mas as demais fontes não devem ser negligenciadas, ao se estabelecer medidas de controle sanitário da doença.…”
Section: Resultsunclassified
“…Since then, PrP was regarded as a newly infectious agent that resulted in zoonosis in human and many animals, and much research attention was focused on this protein. As we all know, many evidences proved that the prion in milk from scrapie affected ruminates can transmit this disease, directly or through the presence of milk derived material in animal feed stuffs [6][7][8][9] . It also raised some concern with regard to the risk to humans of TSE exposure milk from ovine and cow.…”
Section: Progress On Milk Safety In Relation To Prion Proteinmentioning
confidence: 99%
“…Considering of a relative study showed that prion replication occurred in the mammary gland with mastitis within scrapie infected sheep, the foundation of PrP C in milk implied the possibility that milk from TSE infected animals could be served as source for PrP Sc . And it was proposed that this replication could be taken out in sheep mammary gland, because PrP Sc was located in mammary glands [9,41] . In the later, experimental lambs with high susceptible PRNP genotypes (VRQ/VRQ) were fed with milk from scrapie affected ewes, then PrPSc was detected in lymphoid follicles and distal ileum in these lambs, although they had no clinical symptoms, 15 live lambs in experimental group were positive for PrP Sc after seven months, whereas PrP Sc was not detected in the 14 control flock.…”
Section: Milk and The Transmission Of Prp Scmentioning
confidence: 99%
See 1 more Smart Citation
“…The ectopic lymphoid follicles within the mammary glands of sheep with mastitis and coincident scrapie infection can act as ectopic sites of prion replication (Ligios et al, 2005). Furthermore, scrapie-affected sheep with congruent lentiviral mastitis secrete prions into their milk at levels sufficient to transmit disease to suckling lambs (Ligios et al, 2011).…”
Section: Mammary Gland and Mastitismentioning
confidence: 99%